Comparative analysis of Treadmill Walking with different occlusion pressure on aerobic capacity and muscle strength among Sedentary Collegiates- A Randomized Controlled Trial - Gujral, Tanya; Ali, Kamran (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Sedentary lifestyles among college students pose a significant public health challenge, contributing to diminished aerobic capacity and muscle strength. Blood Flow Restriction training (BFRT) has emerged as an effective method to enhance physiological adaptations with low mechanical stress. Aim. This study evaluates the comparative effects of treadmill walking under varying occlusion pressures on aerobic capacity and knee extensors strength in sedentary collegiate. Materials and Methods. Thirty sedentary college students (aged 18-25 years) were randomized into three groups: Group A (low-pressure BFRT at 40 % limb occlusion), Group B (high-pressure BFRT at 60 % limb occlusion), and Group C (control, no occlusion). Participants underwent supervised treadmill walking for 20 minutes, three times per week over four weeks. Outcomes measured pre- and post-intervention included VO₂ max (aerobic capacity) and quadriceps strength. Statistical analysis was performed using SPSS v25.0 with significance set at p<0.05. A one-way ANOVA was employed to compare differences between groups at baseline and post-intervention. Paired t-tests were used for within-group comparisons. Results. Significant improvements were observed in group A&B. Although Group B demonstrated the highest increase in VO₂ max (18 %) and muscle strength (22 %), followed by Group A (13 % and 16 %, respectively), while Group C showed minimal gains (6 % VO₂ max, 8 % strength) with no adverse events occurred in any group. Conclusions. Treadmill walking with BFRT especially at higher occlusion pressures is an effective, safe, and time-efficient intervention to enhance aerobic capacity and knee extensors strength in sedentary young adults. These findings support the integration of individualized BFRT protocols in fitness and rehabilitation settings to counteract inactivity-related deconditioning.